An alternative for pre-treatment of high-strength raw whey wastewaters: submerged membrane bioreactors - Hasar, H; Kinaci, C; Unlu, A (Wiley, 2004)
The direct treatment of whey wastewater at various sludge ages (10-75 days) and high biomass concentration (above 50 g mixed liquor suspended solid (MLSS) dm(-3)) in a submerged membrane bioreactor (sMBR) is described. The chemical oxygen demand (COD) of raw whey varied in the range of 60 and 90 g dm(-3). After feeding the sMBR with raw whey, effluent COD reduced to about 20 g dm(-3). The effluent was free of suspended solids and total coliform bacteria. Total phosphorus (TP) and orthophosphate (Ortho-P) in the influent varied between 204 and 880 mg dm(-3) and between 180 and 620 mg dm(-3), and effluent TP and Ortho-P reduced to 113 and 109 mg dm(-3), respectively. The ammonium and nitrate concentrations in the influent were in the ranges of 3.4 and 120 mg dm(-3) and 10 and 503 mg dm(-3), respectively. The effluent ammonium concentration varied between 17.6 and 198 mg dm(-3) and nitrate concentrations varied between 0.9 and 69 mg dm(-3). Effluent turbidity varied between 23 and 111 FAU (Formazin Attenuation Unit). The results show that sMBR is an effective pre-treatment system for high-strength agro-wastewaters because of its ability to reduce the pollution load. (C) 2004 Society of Chemical Industry.
Keywords: submerged membrane bioreactor; whey; pre-treatment